Recurrence of the world’s largest green-tide in 2009 in Yellow Sea, China:Porphyra yezoensis aquaculture rafts confirmed as nursery for macroalgal blooms - Liu, D.; Keesing, J.; Dong, Z.; Zhen, Y.; Di, B.; Shi, Y.; Fearns, Peter; Shi, P. (Pergamon, 2010)
In the summer of 2008, the world’s largest green-tide occurred in the Yellow Sea, China. The hypothesized cause was the expansion of Porphyra yezoensis aquaculture along the Jiangsu coastline and the re-occurrence of a green-tide in 2009 was predicted. In this study, satellite and field images showed the formation of the June 2009 green-tide which again originated from the Jiangsu coast. The responsible species, its source and biomass accumulation were studied to support the previous hypothesis. Morphological and phylogenetic analysis demonstrated the homology of Ulva prolifera in the 2008 green-tide with the U. prolifera from P. yezoensis aquaculture rafts. About 91–505 kg/ha of U. prolifera was attached to the P. yezoensis aquaculture rafts and a total biomass of 4956 tonnes was estimated during the harvesting of P. yezoensis. This is sufficient to seed a bloom when they are dislodged from the rafts as a result of harvesting practices.